(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2023)
Pension systems created by state governments are a form of material protection of people after the period of their professional activity. In European countries, there are models whose sources of financing are contributions from employees, employers and public funds from the state budget. National pension systems were created and developed in different economic and social conditions, shaping specific solutions in the scope and level of benefits. They are not only a tool of the state’s social policy, but also have a significant impact on the economy and the condition of public finances. The aim of this study is to present the factors and criteria characterizing models of pension systems and to seek answers to the question: is there a model pension system? Based on the discussion, the summary of the work includes recommendations indicating the direction of development of pension systems models. The analysis of the research subject shows that there is no single model of the pension system. Most European countries adapt their pension solutions to their internal economic and social conditions. Countries strive to develop an optimal, financially sustainable pension system to ensure adequate incomes in retirement and enable older people to enjoy a decent standard of living and economic independence.